Fixed Points of (α, F)Ω-Weak Contractions in p-Metric Spaces and Application - Chol Jin Kil; Jong-Chol Choe; Sang-Jin Kim (Journal of Applied Mathematics)
In this paper, we prove the existence and uniqueness of a fixed point of some α-admissible F-contractions in the setting of p-metric spaces. We also give some examples to support the presented fixed point results. Our results improve, extend, and unify many existing theorems in the literature. As an application of the obtained results, we consider the existence of a solution of nonlinear integral equations.